Conflict Resolution Education for Football Supporters from a Political Communication Perspective - Nurgiansah, T Heru; Suryadi, Karim; Danial AR, Endang; Maftuh, Bunyamin; Malihah, Elly; Budimansyah, Dasim (CV. Rayyan Dwi Bharata, 2024)
The rivalry and fanaticism of football fans in Indonesia often leads to clashes, both among supporters and with the police and even football players. The purpose of writing this article is to analyze the causes of football fan riots and their resolution from a political communication perspective. The method used is a literature review. The results of the discussion state that integrating conflict resolution education in a political communication perspective provides a holistic approach to overcoming conflict among football supporters. This can be done in several ways, including leadership, the role of the media, community involvement, advocacy campaigns and training programs.